Living Sunnah and the Implementation of the Prohibition of Domestic Violence in Semarang City - Tumiwa, Anisa Jihan; Nafi’ah, Himmaty Alimatun; AR, Muh. Ahmad Ridha (Antmind Review: Journal of Sharia and Legal Ethics, 2024)
This study analyzes the phenomenon of domestic violence (KDRT) in Semarang City by focusing on public understanding of the hadith prohibiting domestic violence, the implementation of religious values in daily life, and its synergy with positive law. Data shows an increase in domestic violence cases in Semarang City over the past three years, which includes physical, psychological, sexual, and economic neglect. With a descriptive qualitative approach, this study collects data through interviews with judges, advocates, security forces, and the community, as well as analysis of legal documents and related hadiths. The results of the study show that the community has a diverse understanding of the hadith prohibiting domestic violence, depending on the educational and professional background. Although some societies have applied hadith values, the practice is often limited to the prohibition of physical violence, while psychological and economic violence is still frequent. This study also found that the synergy between hadith, positive law, and community legal culture has not been fully realized, so more integrated religious and legal education is needed. Recommendations include increased social campaigns, economic empowerment, and collaboration between legal institutions and religious leaders to create harmonious, prosperous, and violence-free families.